Granger Causality Between Exchange Rate and Stock Price: A Toda Yamamoto Approach - Siami-Namini, Sima (International Journal of Economics and Financial Issues, 2017)
This research article attempts to examine the relationship between exchange rate and stock price using quarterly data of Iran on nominal exchange rate, stock price index, liquidity and consumer price index covering the period of 1994:02 to 2010:01. It also investigates the long-run relationship between variables using Johansen-Juselius (1990) co-integration test and the short-run dynamic causal relationship by using Toda-Yamamoto (1995) procedure. Likewise, variance decompositions (VDCs) serve as tools for evaluating the dynamics interactions and strength of causal relations among variables in the system. The results show that there is no any significant evidence of a relationship between stock prices and exchange rates. Keywords: Exchange Rates, Stock Prices, Johansen-Juselius Co-integration Test, Toda-Yamamoto Causality Test. JEL Classifications: C32, E31, G15